IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE TEXT THROUGH MODELLING TECHNIQUE IN THE SECOND SEMESTER OF THE EIGHT-YEAR STUDENTS OF PUBLIC JUNIOR HIGH SCHOOL 2 BLITAR - Sulaiman, S (International Research-Based Education Journal, 2017)
This action research is aimed at finding out whether modelling technique can help students of year eight SMP Negeri 2 Blitar increase their achievement in writing narrative text, a text which is complex for the students. In finding out the data, the teaching and learning process is designed into two cycles. After all data are obtained, they are then arranged and analyzed. The data analysis yields that modelling technique is significantly increasing the learners’ achievement in writing narrative text. An instrument for collecting data uses questioner, lesson plan and student’s worksheet. After analyzing the data, the writer finally found mean score of the student’s achievement on a narrative text as follow: 70.5 for the first cycle and 80.5 for the second cycle. The score in the first cycle and the score in the second cycle shows clearly significant increase 3,00. Based on the fact above it is proved that modelling technique effectively increases the student’s achievement in writing narrative text. Being proved above it is here suggested that modelling technique is to be used in teaching writing. Consequently, the teachers need to choose suitable approach or strategy in teaching competencies and motivate the students e.g. through selecting actual topics. So that the teaching process runs well and the learning objective is accomplished. Keywords: improving writing skill, narrative text, modelling technique